Astaxanthin anticancer effects are mediated through multiple molecular mechanisms: A systematic review. (May 2020) - Faraone, Immacolata; Sinisgalli, Chiara; Ostuni, Angela; Armentano, Maria Francesca; Carmosino, Monica; Milella, Luigi; Russo, Daniela; Labanca, Fabiana; Khan, Haroon
Graphical abstract: Abstract: During the latest decades, the interest on the effectiveness of natural compounds and their impact on human health constantly increased, especially on those demonstrating to be effective on cancer. Molecules coming from nature are currently used in chemotherapy like Taxol, Vincristine or Vinblastine, and several other natural substances have been showed to be active in reducing cancer cell progression and migration. Among them, astaxanthin, a xanthophyll red colored carotenoid, displayed different biological activities including, antinflammatory, antioxidant, proapoptotic, and anticancer effects. It can induce apoptosis through downregulation of antiapoptotic protein (Bcl-2, p-Bad, and survivin) expression and upregulation of proapoptotic ones (Bax/Bad and PARP). Thanks to these mechanisms, it can exert anticancer effects towards colorectal cancer, melanoma, or gastric carcinoma cell lines. Moreover, it possesses antiproliferative activity in many experimental models and enhances the effectiveness of conventional chemotherapic drugs on tumor cells underling its potential future use. This review provides an overview of the current knowledge on the anticancer potential of astaxanthin by modulating several molecular targets. While it has been clearly demonstrated its multitarget activity in the prevention and regression of malignant cells in in vitro or in preclinical investigations, further clinical studies are needed to assess its real potential as anticancer in humans.